The shape of night : a novel - Gerritsen, Tess (Ballantine Books, 2019)
"A woman trying to outrun her past is drawn to a quiet coastal town in Maine--and to a string of unsolved murders--in this haunting tale of romantic suspense from New York Times bestselling author Tess Gerritsen."--